PERANAN ARAH KIBLAT TERHADAP IBADAH SHALAT - Iman RN, Bustanul (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract:. The scholars of jurisprudence differed in addressing the problems facing the Qibla/ Kaaba. Imam Shafi'i and most of his followers require the Muslims to go to 'ain al-Ka'bah. Medium Jumhur Ulama other than Shafi'iyah for Muslims whose region is far from the Ka'bah is quite facing to jihat al-Ka'bah. While Indonesian Muslims are required to face 'ain al-Ka'bah in performing worship prayer ie to the northwest according to the position of each place, although facing to the West exactly the shalat is still valid. However, if facing to 'ain al-Ka'bah its validity will be more perfect. For that reason for the area of Indonesia mosque kiblatnya less accurate directions to be rearranged shafnya and not have to dismantle the building.